Combine the fractions to get

`1/(x-2)-1/(x^2-4)=(x+2)/(x^2-4)-1/(x^2-4)=(x+1)/(x^2-4).`

As ` ``x->2` from above, the numerator approaches 3 and the denominator is always positive and approaches 0, so the ` `expression grows without bound in the positive direction. That is,

`lim_(x->2^+)(1/(x-2)-1/(x^2-4))=oo.`

Similarly, we can show that` `

`lim_(x->2^-)(1/(x-2)-1/(x^2-4))=-oo,`

** so the limit doesn't exist, even...**

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Combine the fractions to get

`1/(x-2)-1/(x^2-4)=(x+2)/(x^2-4)-1/(x^2-4)=(x+1)/(x^2-4).`

As ` ``x->2` from above, the numerator approaches 3 and the denominator is always positive and approaches 0, so the ` `expression grows without bound in the positive direction. That is,

`lim_(x->2^+)(1/(x-2)-1/(x^2-4))=oo.`

Similarly, we can show that` `

`lim_(x->2^-)(1/(x-2)-1/(x^2-4))=-oo,`

**so the limit doesn't exist, even in the form of `+-oo.` **Remember that the rule for evaluating the limit of the difference of two expressions is valid only if both limits exist. Here, neither `1/(x-2)` or `1/(x^2-4)` has a limit as `x->2` , so the rule isn't valid.